Criteria applicable to the treatment of preventive detention in the context of COVID-19 - APONTE RIOS, Ashlie Melanie (2020)
The research aims to establish criteria for the treatment of the application, extension and termination of preventive detention in a context of a State of Emergency due to COVID-19 in order to strengthen the interpretation of criminal judges. It was developed in an experimental quantitative design, of a descriptive purposeful type, the sample consists of 09 criminal Judges of the Superior Court of Justice of Lambayeque, Province of Chiclayo, 09 Provincial Head Prosecutors of the three Provincial Criminal Prosecutors of Chiclayo and 60 criminal lawyers the Illustrious Lambayeque Bar Association; From the results, it isemphasized that 67% of Judges, 78% of prosecutors and 77% of Lawyers consider that it is important to develop as legal doctrine criteria that complement judicial decisions regarding preventive detention, contextualizing a State of Emergency. In this sense, it was concluded that the issuance of a NationalPlenary Agreement should be proposed that establishes as legal doctrine criteria for application, extension, and termination of preventive detention in a context of COVID-19 that considers international standards, with in order to contribute to improving the criminal procedural justice of the Peruvian State.Keywords: criteria, preventive detention, State of emergency COVID-19.